Long-term portfolio investments: New insight into return and risk - Alexander Abramov (Russian Journal of Economics, 2015)
This article analyzes the impact of the increase of an investment horizon on the comparative advantages of the basic asset classes and on the principles of constructing the investment strategy. It demonstrates that the traditional approach of portfolio management theory, which states that investments in stocks are preferable over bonds in terms of their long-run risk–return trade-offs, is by no means always consistent with empirical evidence. This article proves the opposite, i.e., that for long-term investors, investments in corporate bonds are more profitable in terms of the risk–return ratio than investments in stocks, arguing in favor of strategies pursued by pension funds and other institutional investors focused primarily on investments in fixed-income instruments, including infrastructural bonds. Emphasis is placed on the need for regular adjustments to long-term investors’ portfolios. As portfolios get older, those investors see a reduction in the returns’ dispersion, while differences in risk between various portfolios increase. This means that to maintain a fixed risk–return ratio for a portfolio as the horizon increases, an investor needs to increase the share of lower-risk financial assets during asset allocation process. This thesis becomes especially relevant in the context of retirement savings management.